ELECTRONIC CONTROL OF LOCAL UNIFORMITY OF ILLUMINANCE FROM POWER LED - LISOVENKO Valentin; LISOVENKO Denys Valentynovych; BAZIK Oleksandr; SHMELEV Yurii; BYŁEŃ Sławomir (2020)
It has been suggested to assess non-uniformity of illuminance by the coordinate distribution of its gradient. By the example of mathematical model, the possibility to form a desired illuminance gradient profile from a multicomponent module by means of electronic control of the LED lighting parameters.